Risk factors of accidents with sharp instruments - Luise Nowak, Nicolle; Alves Campos, Gilberto; de Oliveira Borba, Érica; Ulbricht, Leandra; Borba Neves, Eduardo (O Mundo da Saúde, 2013)
Health care professionals are exposed to a number of risks in hospital environment among which biological risk should be highlighted. This research aimed to identify risk factors of accidents with sharp instruments and analyze the main causes mentioned. This is a retrospective exploratory study with a sample of one hundred nursing students already working at a technical level and who had already suffered some sort of accident with sharp instruments. The analysis of the results showed that 41% of the accidents occurred in large hospitals and in the morning shift, the ICU environment was the one with greater prevalence of accidents and the objects that caused most accidents were syringe needles. The causes identified as possible risk factors of accidents indicate the importance of implementing the National Policy on Permanent Education in Health (PNEPS), of using PPE and of the standard precautions